When and How Do Children Start Producing A Languge? - Musliadi Musliadi (Institut Agama Islam Negeri Palopo, 2019)
This article discusses how a child speaks his first language. The first language spoken through several phases is called the semantic process, syntax and phonology. Newborn babies get their first language from their mother called mother tongue. In the process, newborn babies need a lot of interaction both inside and outside the environment to obtain language, including using the five senses to find out the meaning of language acquired from the surrounding. As with animals, humans are born equipped with language acquisition devices (LAD) as the natural abilities of babies used to interpret language and learn languages. This is what distinguishes between humans and animals. By using this LAD, humans are able to communicate or respond to language from others.